2015
DOI: 10.1002/jbm.b.33406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of precursor concentration and spray pyrolysis temperature upon hydroxyapatite particle size and density

Abstract: In the synthesis of hydroxyapatite powders by spray pyrolysis, control of the particle size was investigated by varying the initial concentration of the precursor solution and the pyrolysis temperature. Calcium phosphate solutions (Ca/P ratio of 1.67) with a range of concentrations from 0.1 to 2.0 mol/L were prepared by dissolving calcium nitrate tetrahydrate and diammonium hydrogen phosphate in deionized water and subsequently adding nitric acid. Hydroxyapatite powders were then synthesized by spray pyrolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 12 publications
0
18
1
Order By: Relevance
“…According to the method, reagents and variables adopted, it is possible to obtain materials based on CaP with different phases, which results in materials with diverse characteristics and properties, such as crystalline defects, high surface area, organic material affinity found in physiological medium and so on [46]. HAp can be synthesized by a variety of techniques that can be broadly grouped into six sets of methods: i) dry methods: involve solid state and mechanochemical reactions [63][64][65][66][67]; ii) wet methods: based on low-temperature chemical precipitation [68], co-precipitation [66,69,70], sol-gel route [71][72][73][74][75][76] and hydrolysis [77,78]; iii) hydrothermal methods: use aqueous solutions of high temperature and high voltage, as hydrothermal [79][80][81], emulsion and microemulsion [82,83], and sonochemical [84]; iv) high temperature processes: include combustion [85,86] and pyrolysis [87,88]; v) synthesis based on biogenic sources: can be extracted from fish bones [89], shells [90], eggshells [91,92], bovine bones [93,94], in the presence of biomolecules [95][96][97] or biomembranes [98]; and vi) combination of the aforementioned methods. All methods used for synthesizing HAp particles have different processing characteristics and can result ...…”
Section: Synthesis Of Hydroxyapatitementioning
confidence: 99%
See 1 more Smart Citation
“…According to the method, reagents and variables adopted, it is possible to obtain materials based on CaP with different phases, which results in materials with diverse characteristics and properties, such as crystalline defects, high surface area, organic material affinity found in physiological medium and so on [46]. HAp can be synthesized by a variety of techniques that can be broadly grouped into six sets of methods: i) dry methods: involve solid state and mechanochemical reactions [63][64][65][66][67]; ii) wet methods: based on low-temperature chemical precipitation [68], co-precipitation [66,69,70], sol-gel route [71][72][73][74][75][76] and hydrolysis [77,78]; iii) hydrothermal methods: use aqueous solutions of high temperature and high voltage, as hydrothermal [79][80][81], emulsion and microemulsion [82,83], and sonochemical [84]; iv) high temperature processes: include combustion [85,86] and pyrolysis [87,88]; v) synthesis based on biogenic sources: can be extracted from fish bones [89], shells [90], eggshells [91,92], bovine bones [93,94], in the presence of biomolecules [95][96][97] or biomembranes [98]; and vi) combination of the aforementioned methods. All methods used for synthesizing HAp particles have different processing characteristics and can result ...…”
Section: Synthesis Of Hydroxyapatitementioning
confidence: 99%
“…In spray pyrolysis synthesis, particles are formed through the aerosol process that atomizes a solution and heats the droplets to produce solid particles with no addition of fuel. The precursor solution is sprayed in a flame or in a hot zone of an electric oven by an ultrasonic spray generator [87,88]. Cho et al [87] synthesized HAp powders via spray-pyrolysis and observed that the reduction of precursor concentration and an increase in the spray pyrolysis temperature caused a decrease in particle sizes.…”
Section: High-temperature Processesmentioning
confidence: 99%
“…Therefore, many studies have been published on HAp preparation and investigation of its major properties. Namely, synthetic HAp can be successfully prepared using various experimental techniques, such as sol–gel (Sanosh et al 2009 ), spray pyrolysis (Cho et al 2016 ), solution combustion (Pratihar et al 2006 ), hydrothermal (Manafi and Rahimipour 2011 ), microwave (Ruban Kumar et al 2010 ), precipitation (Mobasherpour et al 2007 ) and extraction from natural resources (Akram et al 2014 ). Among them, sol–gel is an inexpensive method for preparing of the nano-sized HAp, having high crystallinity and purity, at low temperatures (Kalita et al 2007 ; Kaygili and Tatar 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…zone of an electric furnace [32,33] a. Solvothermal process b. Spray pyrolysis Table 1. Shows the key methods for the synthesis of hydroxyapatite (HAp).…”
Section: Requires Organic Solvents and Hotmentioning
confidence: 99%